The effect of playing video games on laparoscopic surgical skills - Murat Baki Yildirim; Mehmet Berksun Tutan; Ramazan Topcu; Murat Bulut Ozkan; Ibrahim Tayfun Sahiner (Medicine Science, 2021)
In this study, it was aimed to reveal whether playing video games had a positive effect on laparoscopic surgical skills. A retrospective analysis was performed on the data of the patients, who underwent laparoscopic cholecystectomy between 01.08.2016 and 01.02.2021. Patients were divided into two groups as patients, who underwent laparoscopic cholecystectomy performed by surgeons who did not play video games (Group I), and patients, who underwent laparoscopic cholecystectomy performed by surgeons who played video games (Group II). The groups were compared in terms of demographic data, ASA scores, duration of surgery, length of stay in the hospital and intraoperative complications. In the study, 449 patients were included in Group I, and 595 patients were included in Group II, after the exclusion criteria were applied. It was observed that there was no significant difference between the two groups in terms of demographic data, ASA scores and intraoperative complications. The mean duration of surgeries performed by surgeons who did not play video games (Group I) was 49.39 ± 18.05 minutes, and the mean duration of surgeries performed by surgeons who played video games (Group II) were found to be 46.74 ± 17.50 minutes, with statistically significance (p= 0.01). Playing video game regularly has a positive effect in terms of ability and speed of laparoscopy. Besides, it is considered to be encouraging in terms of advanced laparoscopic surgical interventions. [Med-Science 2021; 10(3.000): 959-62]